Religious Fanaticism and Changing Patterns of Violent Crime in Nigeria - Enweonwu, Olisa Anthony; Ugwu, Ikenga Patrick; Onyejegbu, Dominic Chukwuemeka; Areh, Chinwe Edith; Ajah, Benjamin Okorie (International Journal of Criminology and Sociology, 2021)
Fanaticism has brewed into different forms in the Nigerian context – and the gravest is religious fanaticism. It has taken hold of most clans, religions, and ethnic groups across Nigeria. Religion has always existed in Nigerian societies and also has fanaticism but the level of violence precipitated by this fanaticism is apparently unprecedented. This paper journeys into the beginning of religious fanaticism in Nigeria and its changing patterns of violence. It highlights the root causes of religious violence in Nigeria and visible patterns in this violence. The paper adopted structural-functionalism theoretical formation and gathered data from textbooks, e-books, journals, online articles, newspapers, and magazines. At the end, the paper recommends that Nigerian governments initiate comprehensive programs to reconcile the religious differences that have evolved over time between Christianity, Islam, and African Traditional Religions.